Effect of Gabapentin and Baclofen on Histology Study in Neuropathic Pain - Fajrin, Fifteen A.; Khotib, Junaidi; Susilo, Imam (Indonesian Journal of Clinical Pharmacy, 2015)
Neuropathic pain resulted from injury to nerves is often resistant to current treatments and can seriously cause chronic pain if no appropriate treatment is given. This study was designed to prove the effectiveness of gabapentin and baclofen in increasing latency time toward thermal stimulus and recovering the morphology of dorsal horn of spinal cord in neuropathic-induced chronic pain. Forty mice were divided into 8 groups i.e sham, negative control, gabapentin at three different doses (10, 30, 100 nmol) and baclofen at three different doses (1, 10, 30 nmol). Neuropathic condition was induced by ligation of sciatic nerve with Partial Sciatic Nerve Ligation (PSNL) method. Gabapentin and baclofen were administrated intrathecally once a day for seven days, a week after neuropathic induction. Latency time toward thermal stimulus was measured on days 0, 1, 3, 5, 7, 8, 10, 12 and 14 after induction. Histology of the dorsal horn of spinal cord tissue was examined by haematoxylline-eosin staining. The results showed that intrathecal injection of gabapentin and baclofen significantly increased latency time of mice toward thermal stimulus compared with negative control. Gabapentin and baclofen are effective as treatment for neuropathic pain. They can also help the recovery process of the histology in dorsal horn in neuropathic pain.Keywords: Baclofen, dorsal horn, gabapentin, neuropathic pain, PSNLEfek Gabapentin dan Baclofen terhadap Studi Histologi pada Nyeri NeuropatiNyeri neuropati berasal dari luka pada saraf yang umumnya sulit diterapi sehingga menyebabkan nyeri kronik bila tanpa managemen terapi yang tepat. Tujuan penelitian ini adalah membuktikan efektivitas gabapentin dan baclofen dalam meningkatkan waktu ketahanan terhadap panas dan memperbaiki morfologi dorsal horn dari spinal cord pada keadaan nyeri kronik yang disebabkan neuropati. Empat puluh mencit terbagi ke dalam delapan kelompok, yaitu sham, kontrol negatif, gabapentin (dosis 10, 30 dan 100 nmol) serta baclofen (dosis 1, 10 dan 30 nmol). Nyeri neuropati diinduksi menggunakan metode Partial Sciatic Nerve Ligation (PSNL). Gabapentin dan baclofen diberikan secara intratekal satu kali sehari selama tujuh hari pada satu minggu setelah induksi nyeri neuropati. Waktu ketahanan terhadap stimulus panas diamati pada hari ke-0, 1, 3, 5, 7, 8, 10, 12, dan 14 setelah induksi. Histologi dorsal horn dari spinal cord mencit diamati menggunakan pewarnaan haematoxylline-eosin. Injeksi intratekalgabapentin dan baclofen meningkatkan waktu ketahanan terhadap stimulus panas secara signifikan dibandingkan kontrol negatif. Gabapentin dan baclofen efektif sebagai terapi nyeri neuropati. Keduanya juga dapat memperbaiki histologi dorsal horn pada kondisi nyeri neuropati.Kata kunci: Baclofen, dorsal horn, gabapentin, nyeri neuropati, PSNL